Subjective Well-Being of the Malaysian Citizen: Preliminary Development of Survey Instrument - Azizan, Nurul Hafizah; Mahmud, Zamalia; Rambli, Adzhar; Abdullah , Nik Nairan; Mahmud, Adzmel (International Journal of Psychosocial Rehabilitation, 2020)
A questionnaire is a well-known measurement instrument used by most of the researchers when conducting a survey. It is a powerful tool for collecting data in survey research. It should be noted that the quality of a measurement instrument used plays a key role in ensuring the quality of data gained in the survey. Therefore, it has become essential for the researchers to carefully design their questionnaire so that the quality of the data obtained can be preserved. Then, it is also vital for the researchers to assess the quality of the data obtained before it can be successfully used for further analysis. This article discussed an early process involved in development of the survey instrument for the purpose of assessing subjective well-being of the Malaysian citizen. These include operationalization of definition, identification of the important dimension and indicators of subjective well-being, rating scale and content validity of the items with the experts.